A Comparative Study Between Laparoscopic Versus Open Incisional Hernia Repair - Alam, Md Noor A; Talukder, Md Rajibul Haque; Iqbal, Md Roushan; Anwar, Raihan; Chowdhury, Humayun Kabir (BIRDEM Medical Journal, 2016)
Aims: This study aims to compare between laparoscopic and open incisional hernia repair. Methods and Materials: The study was conducted in different tertiary hospitals of Dhaka between January 2011 to December 2012 and in 96 patients with incisional hernia. Among them, 68 patients underwent open repair and 28 underwent laparoscopic repair. Both procedures usually consisted of applying a synthetic mesh overlapping the defect. They were followed up for one year to observe the clinical outcome. Results: Mean operative time was shorter in laparoscopic group in comparison to open procedure and mean post operative hospital stay was less than 3 days in laparoscopic group and above 7 days in open group. In the laparoscopic group return to normal activities/work after surgery was less than 2 weeks but after open procedure it was more than 3 weeks. Analgesics requirement was also lower in the laparoscopic group. Post operative complications were observed in 33.82% (23) patients in open hernioplasty group and in 7.14% (2) patients in laparoscopic group which showed significant difference (p<0.05). There was no recurrence in the laparoscopic group during one year follow-up. Conclusion: Data suggest laparoscopic repair is superior to open repair because of less complications, relapses and short hospital stay but long term follow up is required. Birdem Med J 2015; 5(1) Supplement: 29-33